GIONGO DALAM MANGA GEKKAN SHOJO NOZAKI-KUN KARYA IZUMI TSUBAKI - Aditya Muhamad Muldani; Mohammad Ali (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
This study aims to describe the giongo in Gekkan Shojo Nozaki-kun Vol.1 manga based on the type of sound, function, and contextual meaning. The research method used by the author is a qualitative descriptive method. The results of this study found 57 types of giongo onomatopoeias which is “pon” means clapping, “sutt” means fast movement, “bashitt” means slamming, “garatt” means friction, “kyutt-kyutt” means rubbing markers friction, “shatt-shatt” means penctil friction, “shaako-shaako” means bicycle pedaling, “shaka-shaka” means fast bicycle pedaling, “pipiitt” means flute sound, “kashatt” means camera sound. The author hopes that further research can examine other types of onomatopoeias and from a grammatical point of view. Keywords: Onomatopoeia, Giongo, Contextual Meaning, Manga, Gekkan Shojo Nozaki-kun